Selected conditions for endometrial acceptance and preferred forms of psychological asistance - Lewandowska, Bianka (Department of Psychology, University of Wrocław, 2014)
A study of 41 patients was conducted in order to provide an empirical basis for cooperation between a psychologist and a support group of patients with endometriosis. Our aim was to identify psychological variables which have a connection with the disease’s acceptance. The patients’ ages and duration of their illness were taken into account. We demonstrated that there is a positive relationship in accepting the illness through: perceived control and the ability to reduce pain, a declared ability to cope, a sense of harmony with one’s body, and disclosure of negative emotions - mostly anger and sadness. A significantly negative association was shown for: the disease’s duration, coping style with stress concentrating on the emotions, alienation from the body, and “catastrophizing”. Preference for the form of psychological support was also studied. Most preferred were: physician communication training, and individual consultations with a psychologist.
Keywords: endometriosis; acceptance of the disease; chronic illness; coping; body experience